Beragam Metode Memahami Hadis Nabi Saw - Muhammad Zaini (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2023)
The existence of hadiths has not only colored society in various aspects of life, particularly in the academic world, but has also become a continual and fascinating subject of study and research, including approaches and methodologies for understanding and applying hadiths. Nevertheless, comprehending the meaning of a hadith properly can sometimes be relatively challenging. Therefore, the understanding of hadiths has undergone a very long journey, from the time they were spoken and established by the Prophet Muhammad until the present day. The methods used to understand these hadiths have varied from one period to another. This can be understood as a dynamic in the development of human intellectual insight that never ceases over time. The evolution in the understanding of hadiths is also marked by the emergence of various approaches and methods in line with the changing conditions and situations. ABSTRAK Keberadaan hadis tidak hanya telah mewarnai masyarakat dalam berbagai kehidupan, terutama dalam dunia akademisi, akan tetapi juga telah menjadi bahasan dalam kajian dan penelitian yang menarik dan tiada hentinya, termasuk pendekatan dan metodologi pemahaman hadis beserta aplikasinya. Meskipun demikian, untuk memahami maksud suatu hadis secara baik terkadang relative tidak mudah. Oleh karena itu, pemahaman terhadap hadis telah mengalami perjalanan yang sangat panjang, sejak hadis itu diucapkan dan ditetapkan oleh Nabi saw sampai saat sekarang inki. Metode yang digunakan dalam memahami hadis tersebut saling berbeda antara satu periode dengan periode yang lain. Hal ini dapat dimaklumi sebagai suatu dinamika perkembangan wawasan intelektual manusia yang tidak pernah berhenti sepanjang masa. Perkembangan pemahaman terhadap hadis juga ditandai oleh munculnya berbagai pendekatan dan metode sesuai dengan kondisi dan situasi.